The Stray Bullet : William S. Burroughs in Mexico - García-Robles, Jorge, 1956- (Book collections on Project MUSE., 2013)
William Burroughs arrived in Mexico City in 1949, having slipped out of New Orleans while awaiting trial on drug and weapons charges that would almost certainly have resulted in a lengthy prison sentence. Still uncertain about being a writer, he had left behind a series of failed business ventures - including a scheme to grow marijuana in Texas and sell it in New York - and an already long history of drug use and arrests. He would remain in Mexico for three years, a period that culminated in the defining incident of his life: Burroughs shot his common-law wife, Joan Vollmer, while playing William Tell with a loaded pistol. (He would be tried and convicted of murder in absentia after fleeing Mexico.) First published in 1995 in Mexico, where it received the Malcolm Lowry literary essay award, this is an imaginative and riveting account of Burroughs's formative experiences in Mexico, his fascination with Mexico City's demimonde, his acquaintances and friendships there, and his contradictory attitudes toward the country and its culture. Mexico, the author makes clear, was the place in which Burroughs embarked on his "fatal vocation as a writer." Through meticulous research and interviews with those who knew Burroughs and his circle in Mexico City, the author brilliantly portrays a time in Burroughs's life that has been overshadowed by the tragedy of Joan Vollmer's death. He re-creates the bohemian Roma neighborhood where Burroughs resided with Joan and their children, the streets of postwar Mexico City that Burroughs explored, and such infamous figures as Lola la Chata, queen of the city's drug trade. This book also offers a contribution by Burroughs himself - an evocative sketch of his shady Mexican attorney, Barnabe Jurado - as well as previously unpublished letters written by Burroughs from Mexico